Immunosuppressive Properties of Epidermal Keratinocytes Differ According to Their Immaturity Status - Mestrallet, Guillaume; Carosella, Edgardo D.; Martin, Michele T.; Rouas-Freiss, Nathalie; Fortunel, Nicolas O.; LeMaoult, Joel (Frontiers in Immunology, 2022)
Preservation of a functional keratinocyte stem cell pool is essential to ensure the long-term maintenance of epidermis integrity, through continuous physiological renewal and regeneration in case of injury. Protecting stem cells from inflammation and immune reactions is thus a critical issue that needs to be explored. Here, we show that the immature ITA6high precursor cell fraction from interfollicular epidermis keratinocytes, comprising stem cells and progenitors, is able to inhibit CD4+ T-cell proliferation. Of note, both the stem cell-enriched ITA6high / EGFRlow subpopulation and the less immature ITA6high / EGFRhigh progenitors ensure this effect. Moreover, we show that HLA-G and PD-L1 immune checkpoints are overexpressed in ITA6high precursors, as compared to ITA6low differentiated keratinocytes. This potency may limit immune reactions against immature precursors including stem cells, and protect them from exacerbated inflammation. Further exploring this correlation between immuno-modulation and immaturity may open perspectives in allogenic cell therapies.